2017
DOI: 10.5539/ijb.v9n4p1
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Structure of Woody Plants of Sahelian Rangelands of Baban Rafi, Niger

Abstract: The present study investigates the importance of harvesting regimes and natural disturbances on the diversity, the population structure and the regeneration trends of the woody plant species of Sahelian rangelands and their implication for sustainable browsing management. Woody plants data was collected in 42 plots established in the interval of 500 m, along transects distant of 500 m, in the direction South-west and North-east of the study area. In each plot, height and diameter at breast height of each indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…This may also be due to the strong anthropic pressure on this group and therefore the death of adult plants as a result of poor management or overexploitation. Thus, numerous studies carried out in the Sahelian and Sudanian zones have also confirmed this structural variability of species (Rabiou et al, 2015;Idrissa et al, 2017;Amadou et al, 2020). According to Sandjong et al (2018), adaptations to ecological conditions, competition for resources and exploitation would underlie this structural variability.…”
Section: Horizontal Structure Of Edible Fruit Treesmentioning
confidence: 67%
See 1 more Smart Citation
“…This may also be due to the strong anthropic pressure on this group and therefore the death of adult plants as a result of poor management or overexploitation. Thus, numerous studies carried out in the Sahelian and Sudanian zones have also confirmed this structural variability of species (Rabiou et al, 2015;Idrissa et al, 2017;Amadou et al, 2020). According to Sandjong et al (2018), adaptations to ecological conditions, competition for resources and exploitation would underlie this structural variability.…”
Section: Horizontal Structure Of Edible Fruit Treesmentioning
confidence: 67%
“…The low presence of adult individuals with a diameter greater than 15 cm was observed in species with an inverted Jshape that embodies secure regeneration. This indicates that large individuals are heavily exploited as highlighted by Idrissa et al (2017). The 'inverted J' shape type has been observed in T. indica (Fandohan et al, 2011), Dialium guineense (Assongba et al, 2013), Prosopis africana (Houètchégnon et al, 2015) and Lophira lanceolata (Lankoandé et al, 2017).…”
Section: Horizontal Structure Of Edible Fruit Treesmentioning
confidence: 87%
“…The species composition of the field hedges of the study area is relatively poor by comparison with other woody populations in Niger (Mahamane et al 2009;Idrissa et al 2017) with only 16 species registered across the 12 sites over the three years of observation (Table SI 3). This poverty is reinforced by the fact that three species: G. senegalensis, C.…”
Section: 1heterogenous Structures and Homogeneous Species Compositionmentioning
confidence: 86%